DAYA PEMBEDA SOAL, INDEKS KESUKARAN SOAL DAN EFEKTIFITAS OPSI - Murni Ati; Devina Santri; Mariam Nasution (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the concepts and roles of item discrimination index, item difficulty index, and distractor effectiveness as indicators of item quality in educational assessment through a literature review approach. The research was conducted by collecting and analyzing various relevant sources, including books, scientific journals, research articles, and academic documents discussing item analysis. The obtained data were analyzed descriptively to provide a comprehensive understanding of the functions and characteristics of these three aspects. The findings indicate that the discrimination index reflects an item's ability to distinguish between high- and low-achieving students, the difficulty index measures the level of item difficulty, and distractor effectiveness evaluates the functionality of incorrect answer choices in multiple-choice tests. These three components complement one another in determining the quality of assessment instruments, enabling more valid, reliable, and objective measurement of student learning outcomes. Therefore, understanding and applying the analysis of item discrimination, item difficulty, and distractor effectiveness are essential in developing high-quality assessment instruments that support the improvement of teaching and learning processes as well as student achievement.